An Overview of the Latest Applications of Platelet-Derived Microparticles and Nanoparticles in Medical Technology 2010-2020 - Mehrizi, Tahereh Z. (Current Molecular Medicine, 2022)
Today, Platelets and platelet-derived nanoparticles and microparticles have found many applications in nanomedical technology. The results of our review study show that no article has been published in this field to review the current status of applications of these platelet derivatives so far. Therefore, in the present study, our goal is to compare the applications of platelet derivatives and review their latest status between 2010 and 2020 to present the latest findings to researchers. A very interesting point about the role of platelet derivatives is the presence of molecules on their surface, which makes them capable of hiding from the immune system, reaching different target cells, and specifically attaching to different cell types. According to the results of this study, most of their applications include drug delivery, diagnosis of various diseases, and tissue engineering. However, their application in drug delivery is limited due to heterogeneity, large size, and the possibility of interference with cellular pathways in microparticles derived from other cells. On the other hand, platelet nanoparticles are more controllable and have been widely used for drug delivery in the treatment of cancer, atherosclerosis, thrombosis, infectious diseases, repair of damaged tissue, and photothermal therapy. The results of this study show that platelet nanoparticles are more controllable than platelet microparticles and have a higher potential for use in medicine.
Keywords: platelet derivatives